MENGABDI KYRIOS DALAM KAIROS (Suatu Ulasan atas Karya Pastoral Kaum Religius di Keuskupan Agung Medan) - Simanullang, Gonti (UNIKA Santo Thomas, 2004)
It is a task of the Church to tell the world of God's love at whatever time. She is called to be an internally significant and externally relevant Church. How is the Catholic Church able to share a spirituality meaningful and fruitful life with today's people? In order to be able to commit that call, She has to discern the signs of times or kairos. The Catholic Church of Arcdiocese of Medan is also assigned to that task, so that she can give adequate responses to the needs of the faithful and society she faces with. The more she can truely and ecxactly response to the signs of times, the more she can help people to think and act in terms of God. The way of the Church of Arcdiocese of Medan puts them into practise, is the formulation of her vision and mission in the booklet released on March 25th, 2002.